Advances in electrical energy storage using core-shell structures and relaxor-ferroelectric materials - Brown, James Emery (Kansas State University, 2018)
Electrical energy storage (EES) is crucial in todays’ society owing to the advances in electric cars, microelectronics, portable electronics and grid storage backup for renewable energy utilization. Lithium ion batteries (LIBs) have dominated the EES market owing to their wide use in portable electronics. Despite the success, low specific capacity and low power rates still need to be addressed to meet the increasing demands. Particularly, the low specific capacity of cathode materials is currently limiting the energy storage capability of LIBs. Vanadium pentoxide (V₂O₅) has been an emerging cathode material owing to its low cost, high electrode potential in lithium-extracted state (up to 4.0 V), and high specific capacities of 294 mAh g⁻¹ (for a 2 Li⁺/V₂O₅ insertion process) and 441 mAh g⁻¹ (for a 3 Li⁺/V₂O₅ insertion process). However, the low electrical conductivities and slow Li⁺ ion diffusion still limit the power rate of V₂O₅. To enhance the power-rate capability we construct two core-shell structures that can achieve stable 2 and 3 Li⁺ insertion at high rates. In the first approach, uniform coaxial V₂O₅ shells are coated onto electrospun carbon nanofiber (CNF) cores via pulsed electrodeposition. The materials analyses confirm that the V₂O₅ shell after 4 hours of thermal annealing at 300 °C is a partially hydrated amorphous structure. SEM and TEM images indicate that the uniform 30 to 50 nm thick V₂O₅ shell forms an intimate interface with the CNF core. Lithium insertion capacities up to 291 and 429 mAh g⁻¹ are achieved in the voltage ranges of 4.0 – 2.0 V and 4.0 – 1.5 V, respectively, which are in good agreement with the theoretical values for 2 and 3 Li⁺/V₂O₅ insertion. Moreover, after 100 cycles, remarkable retention rates of 97% and 70% are obtained for 2 and 3 Li⁺/V₂O₅ insertion, respectively. In the second approach, we implement a three-dimensional (3D) core-shell structure consisting of coaxial V₂O₅ shells sputter-coated on vertically aligned carbon nanofiber (VACNF) cores. The hydrated amorphous microporous structure in the “as-deposited” V₂O₅ shells and the particulated nano-crystalline V₂O₅ structure formed by thermal annealing are compared. The former provides remarkably high capacity of 360 and 547 mAh g⁻¹ in the voltage range of 4.0 – 2.0 V and 4.0 – 1.5 V, respectively, far exceeding the theoretical values for 2 and 3 Li⁺/V₂O₅ insertion, respectively. After 100 cycles of 3 Li⁺/V₂O₅ insertion/extraction at 0.20 A g⁻¹ (~ C/3), ~ 84% of the initial capacity is retained. After thermal annealing, the core-shell structure presents a capacity of 294 and 390 mAh g⁻¹, matching well with the theoretical values for 2 and 3 Li⁺/V₂O₅ insertion. The annealed sample shows further improved stability, with remarkable capacity retention of ~100% and ~88% for 2 and 3 Li⁺/V₂O₅ insertion/extraction. However, due to the high cost of Li. alternative approaches are currently being pursued for large scale production. Sodium ion batteries (SIB) have been at the forefront of this endeavor. Here we investigate the sodium insertion in the hydrate amorphous V₂O₅ using the VACNF core-shell structure. Electrochemical characterization was carried out in the potential ranges of 3.5 – 1.0, 4.0 – 1.5, and 4.0 – 1.0 (vs Na/Na⁺). An insertion capacity of 196 mAh g-1 is achieved in the potential range of 3.5 – 1.0 V (vs Na/Na⁺) at a rate of 250 mA g⁻¹. When the potential window is shifted upwards to 4.0 – 1.5 V (vs Na/Na⁺) an insertion capacity of 145 mAh g⁻¹ is achieved. Moreover, a coulombic efficiency of ~98% is attained at a rate of 1500 mA g⁻¹. To enhance the energy density of the VACNF-V₂O₅ core-shell structures, the potential window is expanded to 4.0 – 1.0 V (vs Na/Na⁺) which achieved an initial insertion capacity of 277 mAh g⁻¹. The results demonstrate that amorphous V₂O₅ could serve as a cathode material in future SIBs.
Keywords: Lithium ion batteries; Relaxor-ferroelectric; Carbon nanofibers; Amorphous V₂O₅; Sodium ion batteries; Supercapacitors